PERILAKU SOSIAL KEAGAMAAN DOSEN AGAMA ISLAM DALAM KEHIDUPAN DI MASYARAKAT (Studi Atas Kompetensi Sosial Dosen-Dosen Agama Islam Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang) - H. M. Zainuddin (lp2m-uin malang, 2010)
This research focused on the social-religious competency of Islamic studies’ lecturers of Maulana Malik Ibrahim State Islamic University of Malang. Therefore, this research explored the contribution of the lecturers for the social religious activities in the area in which the lecturers have been living for many years. In this research, the researcher uses the qualitative method using a phenomenology approaches. The techniques of collecting data include observation, in-depth-interview and documentation. This research shows that the contribution of Islamic lecturers for social-religious activities can be divided into four typologies or roles: first: lecturers who involved in social Islamic organization act as a kiai, second: lecturers who concern in Islamic preaching actions as preachers or (da’i), third: lecturers who contribute to spread Islamic teaching or (ustadz) and fourth: lecturers who occupied as village staff .